2003
DOI: 10.1002/pon.677
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of cancer: Exploring relationships between conditional goal setting and depression

Abstract: This study explores depression in cancer patients with reference to conditional goal setting (CGS) theory. CGS theory proposes that depressed individuals believe that personal happiness is conditional upon attainment of specific goals (personal CGS). Other individuals may set important goals believing that goal achievement is a necessary prerequisite of social acceptance and approval (social CGS). CGS has been found to contribute to depression in normal populations. 15.2% of the 67 newly diagnosed cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This instrument was designed to measure depression in the general population, and has been used to measure depression in adults 65þ years (Berkman et al, 1986). In line with (Street, 2003), only 18 of the 20 items were used, as two items referred to physical symptoms that may be related to depression and/or physical health problems. The remaining items considered the behavioural and emotional aspects of depressive symptomatology experienced in the previous week.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This instrument was designed to measure depression in the general population, and has been used to measure depression in adults 65þ years (Berkman et al, 1986). In line with (Street, 2003), only 18 of the 20 items were used, as two items referred to physical symptoms that may be related to depression and/or physical health problems. The remaining items considered the behavioural and emotional aspects of depressive symptomatology experienced in the previous week.…”
Section: Methodsmentioning
confidence: 99%
“…Older people with physical illness have higher rates of depression (Murphy, 1982) and studies have also noted the particularly high rate of co-morbidity between depressive disorder and general medical conditions (Moldin et al, 1993). Other studies have shown those suffering from poor physical health do not necessarily become depressed (Street, 2003). For example, Street found that cancer patients were significantly more likely to be depressed if they exhibited the specific goal setting style of Conditional Goal Setting (Street, 2002) irrespective of the burden of illness (Street, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…CGS has received preliminary empirical support as a predictor of depression in child, adolescent, student, older adult, athlete, and cancer patient samples. [31][32][33][34][35][36] Despite face and clinical validity, this theory has not been applied to EDs. Higher-order end-states have been recognized as motivating functions of EDs in cognitive and psychodynamic accounts of illness [37][38][39] and in empirical research, 40,41 and ''goal linking'' cognitions have been recommended as a treatment target by experts in cognitive-behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%